MXene nanomaterials in biomedicine: A bibliometric perspective - Guo, Runying; Hu, Daorun; Liu, Danrui; Jiang, Qingkun; Qiu, Jiaxuan (Frontiers in Bioengineering and Biotechnology, 2023)
Purpose:MXenes are two-dimensional (2D) nanomaterials that comprise transition metal carbides, nitrides and carbonitrides. Their unique nanostructure attributes it a special role in medical applications.However, bibliometric studies have not been conducted in this field. Therefore, the aim of the present study was to conduct a bibliometric analysis to evaluate the global scientific output of MXene in biomedical research, explore the current situation of this field in the past years and predicte its research hotpots. Methods:we utilized visual analysis softwares Citespace and Bibliometrix to analyze all relevant documents published in the period of 2011-2022. The bibliometric records were obtained from the Web of Science Core Collection. Results:A total of 1489 publications were analyzed in this study. We observed that China is the country with the largest number of publications, with Sichuan University being the institution with the highest number of publications in this field.The most publications on MXene medicine research in the past year were found primarily in journals about Chemistry/Materials/Physics. Moreover, ACS Applied Materials&Interfaces was found to be the most productive journal in this field. Co-cited references and keyword cluster analysis revealed that #antibacterial# and #photothermal therapy# are the research focus Keyword burst detection suggested that driven wearable electronics were newly-emergent research hot spots. Conclusion:Our bibliometric analysis indicates that research on MXene medical application remains an active fifield of study.At present, the research focus is on the application of MXene in the field of antibacterial taking advantage of its photothermal properties. In the future, wearable electronics is the research direction of MXene medical application.